Credit and Investment support for the development of Ukraine’s agricultural and economy sector - Victoria Kovalenko; Sergii Sheludko; Valentyna Semenova; Ganna Kotsіurubenko; Svitlana Danylina (Наукові горизонти, 2023)
One of the key problems of the modern agricultural sector of the national economy is the achievement of stable economic growth. In this context, the system of credit and investment support occupies the main place in the expanded reproduction of this priority industry for the economy of Ukraine. The research aims to review the main trends in credit and investment provision of the agrarian sector of the national economy and to determine further investigations in this direction. It has been established that for the formation of an effective system of credit and investment support for the agricultural sector, it is necessary to consider such positions as the influence of bank lending and climate shocks on the investment decisions of farmers, global and regional trends in the direction of the gross accumulation of fixed capital and fixed assets in agriculture, mechanisms for fixing conditions for the transfer of investment resources for use by agro-industrial companies, financial inequality between the urbanized and rural areas. It has been proven that bank lending is the key tool in all forms of credit and investment support for the agricultural sector. This is especially true during the period of martial law in Ukraine. Using the method of economic and mathematical modelling, it can be argued that bank lending is a strategic financial resource in the formation of credit and investment support for the agricultural sector. A system of credit and investment support is proposed, which is primarily based on the improvement of the system of state regulation of the agrarian sector. It has been proven that to increase the level of effectiveness of the system of credit and investment provision of the agricultural sector, attention should be paid to such an instrument as project financing and a review of the very structural composition of the state regulation of agricultural production, considering the practice of European Union. Such approaches can be used by state authorities when developing a strategy for the development of the agrarian sector in the conditions of martial law and the post-war period, as well as making infrastructural changes in the process of interaction between the banking and agrarian sectors of the national economy